Problem of diagnostics of emotional burning out of teachers (The Journal of Psychology and Sociology, 2015)
In article is considered the main results of diagnostics of type of behavior and experiences in professional activity of teachers revealed by design group under the leadership of the prof. U. Shaarshmidt. In addition, the main results of diagnostics the types of behaviors and experiences in professional activity of teachers, that revealed by project group under the leadership of the profes sor of the Potsdam University (Germany) U. Shaarshmidt, from the point of view of allocation, first of all, the teachers of risk group inclined to emotional burning out were considered. The results of research of U. Shaarshmidt’s proj ect group were discussed and analysed from the point of view of the solution of the problem of early diagnostics of emotional burning out of teacher. In particular, results of research of the Potsdam University project group under the leadership of the professor U. Shaarshmidt revealed the following features of behavior and experiences of teachers in the context of professional activity: a healthy type of behavior – G is identified less than at the fifth part of study sample, the risk type of behavior A and B is very high at teachers (for each type of behavior approximately at one third of study sample).Herewith the type of behavior does not depend on the federal land where teacher works and on the form of education (elementary school, comprehensive school, a gymnasium, etc.). The type of behavior depends on a gender (women are more inclined to risk samples of A and B in com parison with men) and on age (the part of risk samples in behavior raises with an increase of length of work). In conclusion the article provides rec ommendations about that it is advisable to periodically check by psycho diagnostic instruments in what extent the psychological protection as the emotional burning out was formed at teacher, it gives the possibility to develop methods for its prevention, that is, the psychological prevention of emotional burning out of pedagogical workers.
Keywords: burnout; emotional burning; pedagogical profession; psy chodiagnostics of emotional burning.